Critical Participatory Looping: An Agencing Process for Mass Customization in Language Education - Murphey, Tim; Falout, Joseph (Linguistik Online, 2012)
Critical Participatory Looping (CPL) (cf. Falout and Murphey 2010; Murphey and Falout 2010) involves returning processed data from surveys or assignments back to students for further reflection and analysis in small groups. CPL affords dialogical interaction among class members (including the teacher), which can encourage them all as agents developing their own self-determination through action—otherwise known as agencing (cf. Murphey 2010, Nelson and Murphey, 2011). In this paper we first describe the kinds of customization that invite agency, then for CPL provide three examples of teaching and researching with it, theorize on its processes and potential, and discuss its correlates with other domains and mass customization.